(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Road Traffic Injuries (RTI) is a leading cause of death, hospitalization, disability and socioeconomic loss in countries. It was estimated that over 1.2 million people died each year on the world roads as a result of road traffic accidents. According to a survey by WHO, more than 3,200 people get killed and over 130 000 injured in traffic every day around the world. Road traffic fatalities constitute 16.6 of all deaths, making this the sixth leading cause of death in India, and a major contributor to socio-economic losses, the disability burden, and hospitalization. During the year 2016, the total 4,80,652 road accidents are reported which causing injuries to 4,94,624 persons and claiming 1,50,785 lives in the country. This means that, on an average 1317 accidents and 413 accident deaths taking place on Indian roads every day or 55 accidents and 17 deaths every hour (Road Accidents in India, 2016). The purpose of this paper is to analyze the situation of fatal road accidents in India and provide ways to minimize the severity and crash risk of road traffic crashes that may be influenced by the road facility or adjacent environment and to identify the crash potential and safety problems of a road project.